Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chen, Chao-Jun; Wu, Yao; Li, Jun-Yun; Zhang, Hai-Wei; Cheng, Hai; Shen, Chuan-Chou; Ning, You-Feng; Yuan, Dao-Xian; Edwards, R. Lawrence; Zhang, Jian; Li, Ting-Yong (Quaternary science reviews, 2025)
The 4.2 ka event was considered a climatic event that influenced ancient cultural transitions during the Middle-Late Holocene. However, whether this was a global climate event, remains controversial. Although some studies have discussed the changes in the Asian summer monsoon during the 4.2 ka event, the climate change patterns in the Yangtze River Basin (YRB) during this period remain unclear. In this study, we utilized multi-proxy (δ18O, δ13C, and Mg/Ca) records from stalagmite YK1306 to reconstruct the climatic changes in the YRB during 3000∼5000 yr BP. Based on comparative analysis of the high-resolution stalagmite records and other geological proxies within this region, the increased precipitation in the YRB during 4300∼4000 yr BP led to frequent flooding disasters, while double droughts occurred during 4000∼3700 yr BP and 4500∼4300 yr BP. Although there are differences in the characteristics of the 4.2 ka event recorded by speleothems across the Asian summer monsoon region, the 4.2 ka event indicated in the δ18O and δ13C records from speleothems in the YRB is inconsistent with the previously defined 4.2 ka event. The transition of El Niño-Southern Oscillation (ENSO) events resulted in the occurrence of flooding and droughts in the YRB during 4500∼3700 yr BP. This study not only provides new evidence of the hydrological changes in the YRB, but also helps evaluate the impact of climate change on civilizations in the YRB in the Late Neolithic.
Gesehen am 10.10.2025